The hidden language: a psycholinguistic perspective - Gómez Marulanda, Francisco Joel (Rastros Rostros, 2011)
This paper is the result of “Languaje, science and technology” research project which was presented as a talk in the XXVI Seminar of literature, linguistics and semiotics. It was done on December 2010 at the Universidad Industrial de Santander, Bucaramanga. This work is intended to provide some reflections concerning to the role investigations are developing to discover new ways and new technologies related with acquisition, developing and improving of language. In this purpose the most important according to the author intention is how to improve communicative skills by training and cognitive tasks well designed and applied in the educative institutions, that will contribute to get better students and beings with a substantial communicative performance. A special emphasis in this psychological approaching is to apply the new PET, FMRI, Mapping technologies to discover which process happen in the brain when people are concerned in performing any task.